MENEROPONG KEPEMIMPINAN DI PERGURUAN TINGGI KEAGAMAAN KATOLIK: STPK-IPI MALANG - adison adrianus sihombing; Maifalinda Fatra (Balai Penelitian dan Pengembangan Agama Jakarta, 2021)
Leadership is an important topic in the world of scholarly research because of the significant role of leadership and very determinant for the success of higher learning institutions. This study aims to examine a problem faced by the Institute of Catholic Pastoral Ministry (STPK-IPI, Sekolah Tinggi Pastoral Katolik – Institut Pastoral Indonesia)in Malang. This research was carried out at the STPK-IPI Malang known as the first institution of this kind. It has become the parent-institution of twenty-three STPKs under a guidance of Indonesian government through the Directorate General of Catholic Community Guidance of the Department of Religious Affairs of the Republic of Indonesia. Despite its age and parent-like status, STPK-IPI Malang has failed to play a role model for other Catholic high learning institutions in Indonesia. . This study used a convergent parallel mixed-method design. It combined qualitative and quantitative research methods by mixing the two methods proporsionarlly. This study uses primary and secondary data. Primary data were obtained through questionnaires, direct observations, FGDs and in-depth interviews. Respondents include STPK leaders, directors of education, permanent lecturers, foundations, students and bishop of Malang. Secondary data were taken from previous studies, documents and online news. Statistical data processing using SPSS software, qualitative data were analyzed through the restatement, description and interpretation stages. This research found that the main difficulty of this high learning institution was the crisis of human resources. In particular, the quality of its leadership is poor. There are three elements of leadership: the Catholic Community Guidance that gives the license-coach, the Head of the STPK and the Foundation. These three elements have not functioned optimally, and there is no grand design for institutional development. As a result, the management and quality of STPK education is poor. This is shown by the acquisition of C accreditation, minimal publications, limited human resources and not being able to compete with other high learning institutions. This study recommends a transformation of leadership so that this Catholic high learning institution may slowly improve its performance and significantly develop into a competitive high learning catholic institution.